Potential of electrolyte-gated transistors for anionic molecule detection: proof of concept using dye solution - Ozório, Maíza S [UNESP]; Rubira, Rafael J G [UNESP]; Vieira, Douglas H [UNESP]; Martin, Cibely S [UNESP]; Constantino, Carlos J L [UNESP] (IOP Publishing, 2024)
The use of electrolyte-gated transistors (EGTs) as sensors can be an advantageous alternative for the detection of anionic molecules due to their capability to detect various ions in solution. In this study, we explore the potential of EGTs as analytical tools for detecting anionic molecules, utilizing a copper phthalocyanine-3,4′,4″,4‴-tetrasulfonic acid tetrasodium salt (CuTsPc) solution as a proof of concept. The results demonstrate the EGT’s capacity in detecting CuTsPc in an aqueous solution, which molecule dissociates into sodium ions (Na+) and CuPc(SO3−)4 ions, leading to high ionic conductivity and the formation of electrical double layers (EDLs). Varying the concentration of the molecule induced alterations in the EDLs, exhibiting good linearity and sensitivity in the transconductance, and a detection limit of 6.0 × 10−8 mol l−1. Transistors employing the CuTsPc solution as electrolyte operated at low voltages and performed better than water-gated transistors (W-GTs). The transconductance (gm ) value for EGTs using CuTsPc solution reached 1.93 mS, while for W-GTs it was around 0.10 mS. Thus, the CuTsPc solution not only serves as a target-molecule in sensor measurements, but also demonstrates potential as an electrolyte in EGTs, thereby assuming a dual role within the device. The main advantage of the EGTs as an analytical tool is their use as a multiparameter device that enables the detection of the analytes using different phenomena that occur at the EDLs interface and which, consequently, changes the device’s performance.
Keywords: anionic molecules; copper phthalocyanine; EGTs; electrical characterization; electrolyte-gated transistor; sensors